2009
DOI: 10.1055/s-0029-1210803
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Changes in Tamoxifen Treated Men with Idiopathic Oligozoospermia

Abstract: Three months of tamoxifen treatment of 43 men with idiopathic oligozoospermia, out of which 20 completed the study, resulted in a significant enhancement of sperm motility, but the improvement of sperm parameters was in no relation to the FSH response to short time tamoxifen treatment. There was a significant increase of testosterone, estradiol, LH, FSH, SHBG, 17 alpha-hydroxy-progesterone and also of 11 beta-hydroxyandrostenedione, an androgen of exclusively adrenal origin, during the treatment and (with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Tamoxifen citrate inhibits hypothalamic estrogen receptors [4]; thus, gonadotropin-releasing hormone (GnRH) secretion is stimulated. As a result of this stimulation, gonadotropin levels increase and stimulate Leydig cells [5], which enhance production of 5 alfa-dihydrotestosterone [6] in the seminiferous T. C. Kadioglu (&) Istanbul University, Istanbul School of Medicine, Istanbul, Turkey e-mail: teoman@kadioglu.org tubules and epididymis [4,[7][8][9]. It is assumed that TC affects the testis by blocking the estrogenic receptors of the Leydig cells and increasing testosterone production by increasing the sensitivity to serum LH [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen citrate inhibits hypothalamic estrogen receptors [4]; thus, gonadotropin-releasing hormone (GnRH) secretion is stimulated. As a result of this stimulation, gonadotropin levels increase and stimulate Leydig cells [5], which enhance production of 5 alfa-dihydrotestosterone [6] in the seminiferous T. C. Kadioglu (&) Istanbul University, Istanbul School of Medicine, Istanbul, Turkey e-mail: teoman@kadioglu.org tubules and epididymis [4,[7][8][9]. It is assumed that TC affects the testis by blocking the estrogenic receptors of the Leydig cells and increasing testosterone production by increasing the sensitivity to serum LH [3,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored hormone levels in the treated groups to further understand the possible mechanism of action of these treatments. Most of the studies have reported improvement in serum FSH and testosterone levels (Török, 1985; Lewis‐Jones, 1987; Hampl et al, 1988; Sterzik et al, 1991, 1993; Krause et al, 1992; Kadioglu et al, 1999). One study reported improvement only in testosterone (Krause et al, 1992), whereas another study reported no improvement in either testosterone or FSH levels (Sterzik et al, 1991).…”
Section: Hormonal Treatments Aimed At Natural Pregnanciesmentioning
confidence: 99%